2016
DOI: 10.1007/s00586-016-4560-y
|View full text |Cite
|
Sign up to set email alerts
|

Staying connected: structural integration at the intervertebral disc–vertebra interface of human lumbar spines

Abstract: Purpose:To investigate the microscopic fibrous integration between the intervertebral disc, cartilage endplates and vertebral endplates in human lumbar spines of varying degrees of degeneration using differential interference contrast (DIC) optics. Weakness at these junctions is considered to be an important factor in the aetiology of disc herniations. Methods:Magnetic resonance images (MRIs) of cadaveric lumbar spines were graded for degeneration and motion segments from a range of degenerative grades isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Our findings indicate that the CEP and vertebra at the inner annulus region are not well-integrated, which is supportive of previous findings [24][25][26] and may explain the weakness of this zone. Because the CEP and inner annulus are structurally integrated, tension at the CEP-bone interface generated during certain spinal movements can avulse the cartilage from the underlying bone ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that the CEP and vertebra at the inner annulus region are not well-integrated, which is supportive of previous findings [24][25][26] and may explain the weakness of this zone. Because the CEP and inner annulus are structurally integrated, tension at the CEP-bone interface generated during certain spinal movements can avulse the cartilage from the underlying bone ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…() and Brown et al. () have demonstrated at the microscopic level a similar mode of anchorage in mature human lumbar discs. Rodrigues et al.…”
Section: Introductionmentioning
confidence: 76%
“…These authors proposed that this branching morphology serves to strengthen the anchorage by increasing the interface area over which shear forces are distributed (Rodrigues et al 2012). More recently, both Liu et al (2015) and Brown et al (2016) have demonstrated at the microscopic level a similar mode of anchorage in mature human lumbar discs. Rodrigues et al (2015) also conducted a fibril-level structural analysis and provided evidence of short range integration between the branched annular sub-bundles and the cartilaginous and vertebral endplate fibrils (Rodrigues et al 2015).…”
Section: Introductionmentioning
confidence: 96%
“…While rim lesions are well-documented, 15,16 the precise failure location of annulus fibers along the tidemark has only been described in biomechanical studies of excised animal tissue 7 and has not been previously described in human spines. Several prior studies have described the tidemark in human spines, 17,18 which is also an important feature of tendon-bone insertions 19 and articular cartilage-bone interfaces. 20 Around the periphery of the disc, the cartilage endplate is calcified throughout its entire thickness, and the tidemark lies between the annulus and this calcified cartilage.…”
Section: Discussionmentioning
confidence: 99%